Revisión documental en países Latinoamericanos de la epilepsia focal en el deterioro cognitivo en adultos con edad media durante los últimos cinco años. (2021)
Epilepsy is a group of nervous system disorders characterized by the predisposition to suffer episodes of abnormal electrical brain activity that cause seizures and other symptoms. In the documentary hermeneutical analysis it is relevant to determine etiologically that focal epilepsy means, episodes of dysfunction of brain activity, causing seizures, begin in a specific area of the brain, later it can spread to this entire organ.